ZrOCl2 as Efficient Lewis Acid for the Condensation Between Dimedone and Aldehydes - Piri, Somayyeh; Reza Poorheravi, Mohammad (Asian Journal of Chemistry, 2010)
Knoevenagel condensation of benzaldehyde and its derivatives with dimedone was carried out over ZrOCl2 and NaNH2. The materials were characterized by 1H and 13C NMR. ZrOCl2 was found to be a good catalyst for double addition of dimedone to aldehyde. The active methylene group of acetone were chosen to react with benzaldehyde and its derivatives. E-4-Phenylbut-3- en-2-one was found to be the only product of mono Knoevenagel condensation reactions.